Polite sender: A resource-saving spam email countermeasure based on sender responsibilities and recipient justifications - Chalee Vorakulpipat (2018)
Currently, most of the existing spam countermeasures are deployed on the email recipient side. However, they cannot diminish the amount of wasteful traffic sent from the SMTP server and the wasteful data storage in the receiver's inbox incurred by spam emails. This paper presents an alternative approach on the sender side in order to overcome these problems and create a bandwidth-saving reduced-storage email system. Additional functions are added to the SMTP server on the sender side to examine whether should allow the particular email sender. If a proper authorization from the recipient has not been granted, the sending SMTP server will not forward the full email message. Instead, it sends the email header together with some additional inquiries for the recipient to authorize this particular sender. Once the authorization is granted, each pair of a given sender and receiver will be kept in a whitelist at the sending SMTP server. The proposed approach can be easily deployed without modifying the existing SMTP protocol stack. The experiment results based on a prototype and data analysis from real email servers demonstrate that the proposed scheme could drastically reduce the amount of wasteful traffic and storage associated with the annoying spam messages. © 2012 Elsevier Ltd. All rights reserved.